Hyperglycemia and hypoglycemia exposure are differentially associated with micro- and macrovascular complications in adults with Type 1 Diabetes. (July 2022) - Mesa, Alex; Giménez, Marga; Pueyo, Irene; Perea, Verónica; Viñals, Clara; Blanco, Jesús; Vinagre, Irene; Serés-Noriega, Tonet; Boswell, Laura; Esmatjes, Enric; Conget, Ignacio; Amor, Antonio J.
Abstract: Aims: Evaluate the relationship between high and low exposure continuous glucose monitoring (CGM)-derived glucometrics and micro- and macrovascular complications in type 1 diabetes (T1D). Methods: Cross-sectional study in T1D without cardiovascular disease (CVD) and with ≥ 1 of the following: ≥40 years, diabetic nephropathy, or ≥ 10 years of diabetes duration with CVD risk factors. Glucometrics were obtained over 14 consecutive days: glucose management indicator (GMI) and proportion of time < 54 (TBR < 54), <70, 70–180 (TIR), >180 (TAR). Carotid plaque was evaluated by ultrasonography. Logistic regression models adjusted for age, sex, and other risk factors were constructed to test the independent associations with chronic complications. Results: We included 152 patients (54.6% men, 48.7 ± 10.0 years-old). Sixty-seven patients had plaque and n = 71 microvascular complications. TAR (OR 1.28 [1.09–1.51]) and GMI (OR 3.05 [1.46–6.36]) were directly associated with the presence of microvascular complications, while TIR had an inverse relationship (OR 0.79 [0.66–0.93]). TBR < 54 was directly associated with the presence of plaque, even after adjusting for 5-year mean HbA1c (OR 1.51 [1.07–2.13]). Conclusions: High-glucose glucometrics were independently associated with microvascular complications. Only low-glucose exposure glucometrics was significantly associated with preclinical atherosclerosis. Our data support the role of hypoglycemia in the development of CVD in this population.